Critical concepts and management recommendations for cutaneous T‐cell lymphoma: A consensus‐based position paper from the Italian Group of Cutaneous Lymphoma. Issue 3 (4th January 2021) - Zinzani, Pier Luigi; Quaglino, Pietro; Violetti, Silvia Alberti; Cantonetti, Maria; Goteri, Gaia; Onida, Francesco; Paulli, Marco; Rupoli, Serena; Barosi, Giovanni; Pimpinelli, Nicola
Abstract: In this paper, we present a review of critical concepts, and produce recommendations on management issues in cutaneous T‐cell lymphomas (CTCLs) of adults. A panel of nine experts was selected for their expertise in research and clinical practice of CTCLs. During an initial meeting, the areas of major concern in the management of CTCLs were selected by generating and rank‐ordering clinical key questions using the criterion of clinical relevance, through group discussion. Recommendations were achieved by multiple‐step formalized procedures to reach a consensus after a comprehensive analysis of the scientific literature. The panel produced recommendations on how to facilitate the clinical suspicion of CTCL; indication of cutaneous biopsy; optimal histological diagnosis, immunohistochemistry and genetic markers; and staging pathway and up‐to‐date therapeutics (with particular focus on new treatments). The critical concept of integration of the different medical expertise in the management of the patients with CTCL was thoroughly examined. These recommendations are intended for use not only by expert centers but above all by "not experienced" dermatologists and hematologists as well as general practitioners.